Sub‐lineages of the SARS‐CoV‐2 Omicron variants: Characteristics and prevention. Issue 3 (16th August 2022) - Xu, Ailan; Hong, Bixia; Lou, Fuxing; Wang, Shuqi; Li, Wenye; Shafqat, Amna; An, Xiaoping; Zhao, Yunwei; Song, Lihua; Tong, Yigang; Fan, Huahao
Abstract: Since the start of the coronavirus disease 2019 (COVID‐19) pandemic, new variants of severe acute respiratory syndrome coronavirus 2 (SARS‑CoV‑2) have emerged, accelerating the spread of the virus. Omicron was defined by the World Health Organization in November 2021 as the fifth "variant of concern" after Alpha, Beta, Gamma, and Delta. In recent months, Omicron has become the main epidemic strain. Studies have shown that Omicron carries more mutations than Alpha, Beta, Gamma, Delta, and wild‐type, facilitating immune escape and accelerating its transmission. This review focuses on the Omicron variant's origin, transmission, main biological features, subvariants, mutations, immune escape, vaccination, and detection methods. We also discuss the appropriate preventive and therapeutic measures that should be taken to address the new challenges posed by the Omicron variant. This review is valuable to guide the surveillance, prevention, and development of vaccines and other therapies for Omicron variants. It is desirable to develop a more efficient vaccine against the Omicron variant and take more effective measures to constrain the spread of the epidemic and promote public health. Abstract : In this article, we described the discovery of the Omicron variant, biological characteristics of the Omicron variant, immune escape, mutations, patients' clinical features, vaccination, detection methods, treatment with drugs and neutralizing antibodies, and protective measures taken. It is desirable to develop a more efficient vaccine against the Omicron variant and take more effective measures to contain the spread of the epidemic and promote public health.